Fault current handling in large-scale MMC-HVDC systems: an improved approach with DC circuit breaker and fault current limiter - Chandio, Rashid Hussain; Shah, Madad Ali; Memon, Abdul Aziz; Ali, Khawaja Haider; Soomro, Jahangeer Badar; Alamri, Basem; Althobaiti, Ahmed; Alqarni, Mohammed (Frontiers in Energy Research, 2025)
Designing Voltage Source Converter (VSC)-based DC grids presents a significant challenge in providing dependable and cost-effective protection against short-circuit faults. Given the increased vulnerability of high-voltage DC (HVDC) lines to the faults, there is a dire need for enhanced protection equipment capable of effectively handling fault currents. By limiting the rapid increase in fault current, fault current limiters (FCLs) reduce the requirement for complex DC circuit breakers (DCCBs) design in order to isolate faults. This paper presents a novel Hybrid FCL for the protection of large scale VSC-HVDC. It provides a comprehensive analysis of DCCBs and their impact on VSC-HVDC projects with and without FCLs. It further analyses an extensive discussion comparing DCCBs equipped with FCLs to those without FCLs. For simulation analysis, an equivalent circuit modeling approach of the Zhoushan HVDC Project is used to analyze current behavior of FCL-equipped breakers. The paper presents the circuit diagram and operational principles of the proposed FCL. Subsequently, it analyzes the FCL performance with its current limiting features and outlines the parameter design requirements necessary for its implementation. Simulation results utilizing PSCAD/EMTDC are provided to validate various aspects of this research. Further, the performance of the proposed FCL is compared with existing solutions proposed in the literature. From theoretical and simulation validations, it is concluded that DCCBs equipped with FCLs outperform conventional DCCBs without FCLs for higher-rated VSC-HVDC projects.